A generalized common‐ground single‐switch continuous input‐current boost converter favourable for DC microgrids. (26th July 2020) - Varesi, Kazem; Ghorbani, Mahdi
Summary: The conventional DC‑DC converters have limited voltage gain at moderate duty cycles. In theory, the large duty cycles should be adopted to reach large boosting factors. But in reality, at extreme duty cycles, the effect of parasitic components become dominant, which leads to increased voltage drops on devices, increased total loss and reduced efficiency. This paper proposes a single‐switch (requiring single gate‐driver circuit) diode‐inductor‐capacitor (DLC) cell‐based basic boost configuration that can solve the abovementioned issues. The employment of single‐switch has led to only two operational modes (in continuous conduction mode [CCM]) and easy control strategy. The continuous input‐current and large step‐up capability make the proposed configuration favourable for renewable or hybrid energy systems in DC microgrids. The simple configuration, modularity, moderate blocking voltage on semiconductors, wide duty‐cycle range, large voltage gains at low duty cycles, common‐ground between source and load are some profits of suggested configuration. The basic topology can be expanded by addition of DLC cells. Based on comparative analysis, the proposed configuration has larger step‐up capability per required components and lesser average normalized blocking voltage on semiconductors compared with other single‐switch topologies. This leads to smaller and cheaper structure with fewer losses. The configuration and operational modes of proposed basic topology (and its extended version) have been explained. Then, the design considerations and small‐signal modelling of basic topology have been investigated. Finally, the effectiveness and correct operation of proposed topology have been certified by comparative analysis and experimental results. Abstract : This paper proposes a single‐switch diode‐inductor‐capacitor cell‐based basic boost configuration that benefits from (1) continuous input‐current, large gain and maximum power point tracking capability (necessary for PV applications), (2) modular structure and simple structure, (3) easy control, (4) moderate blocking voltage on semiconductors, (5) wide duty‐cycle range and large voltage gains at low duty cycles, (6) large gain per devices and (7) common‐ground between source‐load.